Jihad: Memperebutkan Makna Perang Suci - Khamami Zada (Ulumuna, 2006)
Jihad is nowadays often misunderstood and misused, especially by militant Moslems translating it as a fight against unbelievers in order to destroy them and/or to convert them to Islam. Such a view has reduced the real meaning of jihad. In the time of Muhammad, jihad was not necessarily acted as a fight against the “enemy” of God or the holy war as it is being widely understood today. It was applied as a hard effort to establish Islamic values in society. This article is all about the reduction and misunderstanding of jihad among moslems and nonmoslems. It delivers a historical analysis of view shifting on jihad, from its,wider meaning to its specific one that is using forces and practicing violance. It also launches some cases of misuse of jihad in society from its precedent to modern era. This article suggests a way back to the meaning of jihad as it was.